2009
DOI: 10.1002/j.2333-8504.2009.tb02164.x
|View full text |Cite
|
Sign up to set email alerts
|

Models for Effective and Scalable Teacher Professional Development

Abstract: The minute-to-minute and day-by-day use of assessment for learning holds great potential to change the trajectory of student learning in U.S. classrooms. But without effective and scalable systems of professional development that actually lead teachers to adopt these practices, the utility and impact of assessment for learning will be quite limited. Drawing on learning theory, expertise research, and research on effective professional development, this paper presents the theoretical and empirical basis behind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The requirement that every teacher participate does not always go down easily in the United States, where it simply is not customary for teachers' practice to be exposed to others, unless it is done voluntarily. But, as Black et al (2003) noticed, and has been confirmed in U.S. research on this model of professional development (Lyon, Wylie, & Goe, 2006;Thompson & Goe, 2006), for teachers, knowing they will be expected to report on their most recent efforts is often what motivates them to follow through on trying out some aspect of AfL. So one function of the How's It Going?…”
Section: Superstep A: Teachers Learn Extensively and Deeply About Minmentioning
confidence: 95%
See 1 more Smart Citation
“…The requirement that every teacher participate does not always go down easily in the United States, where it simply is not customary for teachers' practice to be exposed to others, unless it is done voluntarily. But, as Black et al (2003) noticed, and has been confirmed in U.S. research on this model of professional development (Lyon, Wylie, & Goe, 2006;Thompson & Goe, 2006), for teachers, knowing they will be expected to report on their most recent efforts is often what motivates them to follow through on trying out some aspect of AfL. So one function of the How's It Going?…”
Section: Superstep A: Teachers Learn Extensively and Deeply About Minmentioning
confidence: 95%
“…These phases and the research and development process that led to their current structure within KLT are explained in detail in an earlier paper by Thompson and Goe (2006), from which much of the following discussion is drawn.…”
Section: Two Phases Of Professional Learningmentioning
confidence: 99%
“…Deserving special mention was Braun's (2005) report "Using Student Progress to Evaluate Teachers: A Primer on Value-Added Models," which called attention to the problems with this approach. Finally, a third work stream targeted professional development, including enhancing teachers' formative assessment practices (Thompson and Goe 2009;Wylie et al 2009). …”
Section: Teacher and Teaching Qualitymentioning
confidence: 99%
“…As discussed in Thompson and Goe (2008), several models for implementation and delivery have been piloted during the past two years. One main component of each of these models was the establishment of TLCs.…”
Section: How To Change: Teacher Learning Communities (Tlcs)mentioning
confidence: 99%